(untitled) (The Journal of Psychology and Sociology, 2020)
The article describes the theoretical approaches of a number of scientists, philosophers and psy-chologists who have studied the problem of the development of gaming addiction in a person who is overly fond of gambling in a casino. The factor of excessive passion for gambling leads to the destructive development of consciousness and self-consciousness. In a number of modern psychological studies, this problem appears to be an actual due to the widespread recognition of the destructive effects of gambling on the psyche, consciousness and personality. The article is devoted to the study of “psychological characteristics of a person prone to gambling.” Purpose of the study: consideration of personality features of people predisposed to dependence on hazardous games and working out recommendation concerning game dependence prevention, psycho-logical correction and overcoming. The scientific significance of the study: the work reveals personality features of the person predis-posed to dependence on hazardous games are revealed and characterized. The content of behavioral and social determination of occurrence and development of personality psychological dependence to-wards hazardous games is opened. Practical importance of research: on the basis of the received results practical recommendations concerning preventive work with the people predisposed to psychological dependence on hazardous games are worked out. Novelty of the research - a psychological analysis of the phenomenology of the involvement of young people in gambling, leading to the emergence and development of various forms and states of gambling addiction, is carried out. Research Methods: 1) “Test for addiction”, M. Murto, I. Nimela; 2) self-actualization questionnaire A. Maslow; 3) adapt-ed characterological questionnaire of K. Leonhard - G. Schmishek; 4) the scale of reactive (situational) and personal anxiety of C. D. Spilberger - Yu. L. Khanin. The study value: 1) empirically were revealed and characterized social determinants and psychologi-cal features of personality inclined to hazardous games; 2) for the first time revealed the interrelation of personality orientation towards game activity character in connection with parity objective and subjec-tive determinants of person’s game activity; 3) temperament types peculiar for game-dependent and game independent people in connection with individual-psychological signs of situational and personal anxiety were revealed. The revealed properties of psychological characteristics of the person predisposed towards involve-ment to hazardous games can be accounted while working out educational curriculums of disciplines «Psychology of Personality», «Social Psychology», «Judicial Psychology» and «Medical Psychology». Key words: persona, hazardous games, addictive behavior.